2014
DOI: 10.1590/0103-8478cr20130606
|View full text |Cite
|
Sign up to set email alerts
|

Potencial agronômico e teor de carotenoides em raízes de reserva de mandioca

Abstract: RESUMO Os programas de melhoramento genético de mandioca de mesa estão focados na seleção de variedades com a presença de carotenoides nas raízes de reserva. O trabalho foi realizado com o objetivo de avaliar o potencial agronômico e o teor de carotenoides em raízes de reserva de acessos de mandioca com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
(17 reference statements)
3
11
1
10
Order By: Relevance
“…These results can be considered low when compared to those found by Couto (2013) and Silva et al (2014), which evaluated different cassava clones and found mean starch contents of 25.14% and 24.69%, respectively, by means of acid hydrolysis and hydrostatic balance. In addition to the genetic diversity, variation between starch contents can be explained both by the different environmental conditions and the different methods of quantification employed.…”
Section: Starchcontrasting
confidence: 76%
See 1 more Smart Citation
“…These results can be considered low when compared to those found by Couto (2013) and Silva et al (2014), which evaluated different cassava clones and found mean starch contents of 25.14% and 24.69%, respectively, by means of acid hydrolysis and hydrostatic balance. In addition to the genetic diversity, variation between starch contents can be explained both by the different environmental conditions and the different methods of quantification employed.…”
Section: Starchcontrasting
confidence: 76%
“…Although the percentage of starch is more important in the selection of genetic material for the industry, this is also taken into account in the improvement of tamed cassava, especially when considering the use of roots for the manufacture of starch and flour (Silva et al, 2014), as well as the culinary characteristics demanded by the market.…”
Section: Varietiesmentioning
confidence: 99%
“…The selected cultivars must have storage roots with hydrocyanic acid contents less than 100 mg kg -1 fresh roots; high root yield; roots with good sensory properties (softness and plasticity after cooking, nonsticky mass, pleasant aroma and appearance) and cooking qualities (low fiber, low cooking time, and homogeneous mass after cooking); resistance to pests and diseases; architecture favorable to cultural traits (not branching or branching as high as possible); roots with low postharvest deterioration; earliness (harvest up to 11 months), among other characteristics (Vieira et al, 2013). In addition to carbohydrates, cassava has genetic potential to be a source of carotenoids for human consumption, especially β-carotene, a precursor of vitamin A, present in genotypes with yellow roots (Chávez et al, 2005;Mezzete et al, 2009;Silva et al, 2014). Besides being a source of calories for the world's poorest populations, the possibility of cassava being a source of vitamin A would improve the nutrition of these people and add value to cultivars intended for human consumption (Carvalho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Results of physic-chemical characterization of cassava germplasm were previously obtained and a significant difference among the chemical composition of different genotypes has been verified (Chávez et al, 2005;Padonou et al, 2005;Charoenkul et al, 2011;Silva et al, 2014;Sánchez et al, 2014).…”
Section: Introductionmentioning
confidence: 81%